1998
DOI: 10.1210/en.139.12.5144
|View full text |Cite
|
Sign up to set email alerts
|

Functional Maturation of the Primate Fetal Adrenal in Vivo: 3. Specific Zonal Localization and Developmental Regulation of CYP21A2 (P450c21) and CYP11B1/CYP11B2 (P450c11/Aldosterone Synthase) Lead to Integrated Concept of Zonal and Temporal Steroid Biosynthesis

Abstract: Previous studies in the primate fetal adrenal gland have indicated that the gland is comprised of three functional zones: 1) the inner fetal zone (FZ), which has the enzymes necessary for dehydroepiandrosterone sulfate (DHEAS) production beginning early in gestation; 2) the transitional zone (TZ), which possesses enzymes necessary for cortisol production; and 3) the outer, definitive zone (DZ), which appears to function as a reservoir of progenitor cells that may populate the remainder of the gland and does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 0 publications
5
43
0
Order By: Relevance
“…These results are in accordance with previous studies that have reported high levels of aldosterone in neonates (10) compared with their mothers (21). Although aldosterone has been previously shown to cross the placental barrier from the mother to the fetus (20), highest aldosterone levels detected in the cord blood are consistent with de novo synthesis in the fetal adrenal gland, given the very early expression of the aldosterone synthase gene starting from 13 gestational weeks (22). These findings indicate an autonomous regulation of corticosteroid hormone biosynthesis in the fetus, even though the high renin levels in cord blood are likely explained by placental biosynthesis (23).…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with previous studies that have reported high levels of aldosterone in neonates (10) compared with their mothers (21). Although aldosterone has been previously shown to cross the placental barrier from the mother to the fetus (20), highest aldosterone levels detected in the cord blood are consistent with de novo synthesis in the fetal adrenal gland, given the very early expression of the aldosterone synthase gene starting from 13 gestational weeks (22). These findings indicate an autonomous regulation of corticosteroid hormone biosynthesis in the fetus, even though the high renin levels in cord blood are likely explained by placental biosynthesis (23).…”
Section: Discussionsupporting
confidence: 92%
“…Little difference was found between male and female adults except for the metabolites of progesterone, 17OHP and estrogen (data not shown). Increased amounts of metabolites of pregnenolone and DHEA in newborn infants are of fetal cortex origin, with fetal cortex expressing higher P450scc and P450c17 and lower 3b-hydroxysteroid dehydrogenase activities [17][18][19][20]. Increased amounts of 16a-hydroxy metabolites of pregnenolone and DHEA and of 6b-hydroxy metabolite of corticosterone in newborn infants were due to higher P4503A7 activity in the fetal liver.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the human and nonhuman (rhesus monkey) primate fetus have indicated that the adrenal gland comprises three functional zones: 1) the large, inner FZ, which has the enzymes necessary for dehydroepiandrosterone sulfate production beginning early in gestation; 2) the TZ between the inner FZ and outer DZ, which possesses enzymes necessary for cortisol production beginning in late gestation; and 3) the outer, DZ, which appears to function as a reservoir of progenitor cells, which may populate the remainder of the gland, and does not acquire a steroidogenic phenotype with the capacity to produce mineralocorticoids until near term (1, 2, 6 -13). Recently, we have shown that timing of the induction of 3␤HSD in the TZ and CYP11B-ir in the DZ are coincident with increased circulating concentrations of cortisol and aldosterone in late gestation (12). These data suggest that functional maturation of the fetal adrenal cortex is dependent on the specific zonal expression of 3␤HSD and CYP11B, which are pivotal enzymes in adrenal steroidogenesis (1,2).…”
mentioning
confidence: 85%